PERANAN KREDIT USAHA RAKYAT (KUR) PADA PERKEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM): (Studi Kasus pada UMKM Minuman Kekinian di Daerah Jakarta Selatan) - Khafifah, Aura; Dianta, Karunia; Saparuddin (Transpublika Publisher, 2022)
This study aims to determine the influence of KUR funds (People's Business Credit Loan Capital) on the expansion of MSMEs in the South Jakarta Region. This approach combines a qualitative framework with a descriptive approach. The research lasted two months, beginning in February 2022 and concluding in March 2022 in South Jakarta's, especially on modern beverage SME sector. This study discovered that the financing of BRI KUR funds for modern beverage MSMEs in South Jakarta was highly effective. Currently, beverage vendors acknowledge that after receiving KUR funds from BRI, their businesses are expanding, beginning with an increase in revenue and an expansion of the necessary infrastructure. This is due to the fact that the financing of KUR funds by BRI not only provides assistance in the form of funds, but also monitors the growth of each MSME business, making MSME business owners feel extremely supported. The role of KUR financing in the development of modern beverage MSMEs in the South Jakarta region can boost business productivity, particularly for Tebet, South Jakarta-based MSMEs. This demonstrates that the KUR funds provided by BRI have a positive effect on the growth of MSMEs, as initial profits and profits after receiving KUR funds are always higher than initial profits.